Medium-Term Outcomes Using Fresh Osteochondral Allograft Transplantation for Treatment of Large Osteochondral Lesion of the Talus. Issue 1 (19th August 2016) - Rungprai, Chamnanni; Hartog, Taylor Den; Patterson, Jason A.; Amendola, Annunziato
Category: Ankle Introduction/Purpose: Osteochondral allograft has been proven to be successful surgical option for treatment of large osteochondral defect of the talus. However, there are currently limited literatures reported outcomes of this technique. Methods: Retrospective Chart review with prospectively collected data of 26 patients with 26 ankles who had been diagnosed with large osteochondral lesion of the talus and underwent fresh osteochondral allograft transplantation 2004 and 2011 in single institution. All patients had failure of conservative treatment and minimum follow-up to be included in this study was 1 year (mean 40.9 months, range, 12 to 123 months). Pre- and post-operative pain (Visual Analog Scale (VAS)), SF-36 (PCS and MCS), and Foot Functional Index (FFI) were obtained and compared using Wilcoxon Singed-Ranks test. Results: Twenty-six patients (13 male and 13 female) with mean age of 31.7 years and an average of BMI of 29.0 were included in this study. Complete pre-operative and 1-year post-operative pain (VAS) (n=19/26) and functional outcome scores (SF-36 and FFI)(n=12/26) were collected. The mean pain (VAS) decrease from 6.9/10 to 4.8/10 post-operatively (p = 0.007). The mean SF-36 (PCS and MCS) were 41.3 and 54.7 pre-operatively which improved to 47.2 and 56.0 post-operatively, p = 0.084 and p = 0.875, respectively. The mean FFI (pain, disability, activity limitations, and total score) were 48.0, 48.8, 57.6, and 45.8 pre-operatively which changed to 53.4, 57.6, 68.5, and 54.6 post-operatively (p = 0.674, 0.575, 0.110, and 0.859, respectively). There were 61.8% patient satisfaction with this surgery and 82.7% of the patients will do the surgery again and they will recommend this type of surgery to their friends and family. There were 100% survival rate at 5-year (8 of 8) and 10-year (1 of 1). Conclusion: Osteochondral allograft demonstrated significant relief of pain in medium-term of follow-up as measured with VAS. This procedure was successful for treatment of large osteochondral lesion of the talus.